(Invited) Deep-Level Analysis of Passivation of Transition Metal Impurities in Silicon. (23rd July 2018) - Mullins, J.; Markevich, Vladimir; Leonard, S.; Halsall, M.P.; Peaker, A.R.
Abstract : The transition metals (TMs) from 3d and 4d series are very effective recombination centers in silicon. They are harmful for some electronic devices and Si solar cells and should be either neutralized or removed from active areas of the devices. Some of the TMs have low diffusivities, so their gettering is difficult. In this paper we present experimental results on the interactions of transition metals with hydrogen atoms in silicon and on passivation by the displacement of the metals from the interstitial to the substitutional site. The results have been obtained by means of deep level transient spectroscopy. We have studied iron, titanium and vanadium from the 3d series, and Mo from the 4d series. It is found that in the presence of excess vacancies 3d TMs tend to move to substitutional sites and are quite stable in this position with no or much reduced recombination activity and reduced diffusion. Hydrogen reactions with TMs are found to be dependent on the charge states of the reacting species. It is shown that H-TM reactions in p-type Si can be facilitated by manipulating charge states of the reacting species using several techniques.